Adding MR Diffusion Imaging and T2 Signal Intensity to Neck Imaging Reporting and Data System Categories 2 and 3 in Primary Sites of Postsurgical Oral Cavity Carcinoma Provides Incremental Diagnostic Value - Jajodia, A.; Mandal, G.; Yadav, V.; Khoda, J.; Goyal, J.; Pasricha, S.; Puri, S.; Dewan, A. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: The NI-RADS lexicon doesn't use ADC parameters and T2 weighted signal for ascribing categories. We explored ADC, DWI, and T2WI to examine the diagnostic accuracy in primary sites of postsurgical oral cavity carcinoma in the Neck Imaging Reporting and Data System (NI-RADS) categories 2 and 3.MATERIALS AND METHODS: We performed a retrospective analysis in clinically asymptomatic post-surgically treated patients with oral cavity squamous cell carcinoma who underwent contrast-enhanced MRI between January 2013 and January 2016. Histopathology and follow-up imaging were used to ascertain the presence or absence of malignancy in subjects with “new enhancing lesions,” which were interpreted according to the NI-RADS lexicon by experienced readers, including NI-RADS 2 and 3 lesions in the primary site. NI-RADS that included T2WI and DWI (referred to as NI-RADS A) and ADC (using the best cutoff from receiver operating characteristic curve analysis, NI-RADS B) was documented in an Excel sheet to up- or downgrade existing classic American College of Radiology NI-RADS and calculate diagnostic accuracy.RESULTS: Sixty-one malignant and 23 benign lesions included in the study were assigned American College of Radiology NI-RADS 2 (n = 33) and NI-RADS 3 (n = 51) categories. The recurrence rate was 90% (46/51) for NI-RADS three, 45% (15/33) for NI-RADS 2, and 73% (61/84) overall. T2WI signal morphology was intermediate in 45 subjects (53.5%) and restricted DWI in 54 (64.2%). Sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the American College of Radiology NI-RADS were the following: NI-RADS (75.4%, 78.3%, 90.1%, 54.5%, and 76.1%); NI-RADS A (79.1%, 81.2%, 91.9%, 59.1%, and 79.6%); and NI-RADS B (88.9%, 72.7%, 91.4%, 66.7%, and 85.1%), respectively.CONCLUSIONS: Adding MR imaging diagnostic characteristics like T2WI, DWI, and ADC to the American College of Radiology NI-RADS improved diagnostic accuracy and sensitivity.ACRAmerican College of RadiologyAUCarea under the ROC curveCEcontrast-enhanced CTHNSCChead and neck squamous cell carcinomaNI-RADSNeck Imaging Reporting and Data SystemNPVnegative predictive valuePPVpositive predictive valueROCreceiver operating characteristic